The influence of Mobile Legends toward students in enhancing English Language skills: A case study - Waqidah, Siti Nur; Fajar, Dwi Ario (Privietlab, 2025)
This study aims to examine how playing Mobile Legends influences students' English language skills, understand which specific skills (listening, speaking, reading, or writing) show the most significant improvement, and compare the positive and negative effects of the game on English language learning. This research adopts a qualitative approach using a case study method. Data was collected through online questionnaires, semi-structured interviews with selected students, and Duolingo English Test (practice version) scores to assess language proficiency. The study found that Mobile Legends significantly contributes to English language proficiency, particularly in listening and reading skills, by providing authentic and interactive language contexts. Students show increased confidence and motivation. However, negative impacts include potential game addiction and limited exposure to formal grammar. This study can be useful in education by providing insights into integrating informal learning tools like mobile games into classroom learning for more interactive and engaging experiences. Practically, it offers guidance for educators to leverage students' interest in games to improve English language skills. Academically, it contributes to the field of game-language interaction and serves as a basis for further research. This study provides new perspectives on how digital media, often seen as mere entertainment, can be effectively utilized to support language learning in an immersive manner, especially among vocational high school students. It comprehensively evaluates the impact of Mobile Legends on various language skills beyond vocabulary and writing, filling a gap in existing research.